Mobile Phone usage by Micro and Small Scale Enterprises in Semi-Rural Ghana - kwakwa, Paul Adjei (International Review of Management and Marketing, 2012)
This work looked at the use of mobile technology among entrepreneurs/managers of micro and small scale businesses in the Akuapem North district of Ghana. The major findings were that entrepreneurs/business managers would use more than one mobile phone and/or subscribed to more than one network in order to make affordable calls, to enjoy excellent service from other network providers, for business purposes, security reasons and to have a place for their many contact numbers. Apart from marketing/sales purposes, the managers/entrepreneurs used phone for the gathering of information, for product delivery/procurement and managing internal affairs among others. A Chi square test confirmed that mobile phone has helped businesses improve customer services, improve communication with suppliers/customers, open up new branch, keep up with competitors and help increase profit. However, the respondents identified a number of occasional challenges such as no reception, poor sound/breaking up of sound and calls ending unexpectedly. Keywords: Mobile phones; Semi-rural; Ghana; MSEs JEL Classifications: D83; 018; L3